PEMBAGIAN HARTA WARISAN PADA MASYARAKAT MUSLIM DESA SUGIHAN KECAMATAN TENGARAN KABUPATEN SEMARANG - Setiadi, Wahyu (Unnes Civic Education Journal, 2017)
Abstract: This study is aimed to determine the law used in the distribution of inheritance and the reason of implementing its law of Muslim society in the Sugihan Tengaran village. This study used a qualitative research method. The subject of research is the village apparatus, Muslim society of Sugihan Village, and the public figures. The technique of collecting data was using interviews and documentation. The results of this study indicated that the distribution of inheritance in the Sugihan village used Customary Inheritance Law. The reason in choosing the customary inheritance law of Sugihan society was that customary inheritance law enforcement has been done for generations and believed to better reflect the sense of justice and carried through an agreement in order to create harmony among the heirs. The distribution of inheritance can be held when the testator was still alive in a way of grant, or after the testator's death. The timing of the distribution of inheritance was usually carried out after 100 days (Nyatus) of the testator's death by way of meeting of whole heirs and witnessed by testator's relatives or village apparatus. The distribution of inheritance before the testator's death depended on the initiative of the heirs. The main heir is the child, with the male inheritance heirs more than the female called as Sepikul Segendong. The distribution of inheritance used individual inheritance system.